Diagnosis and management of cold urticaria in cryoablation of atrial fibrillation: a case report. Issue 4 (16th December 2019) - Cordes, Friederike; Ellermann, Christian; Ehrchen, Jan; Ullerich, Hansjoerg; Eckardt, Lars
Abstract: Background: Cold-induced urticaria is triggered by exposure to local or environmental cold and manifests as localized or systemic pruritic papules, sometimes accompanied by angio-oedema and anaphylaxis representing a life-threatening condition. Therapy options of atrial fibrillation (AF) include catheter ablation with different energy sources, of which cryoenergy may be superior to other energy sources regarding safety and efficacy. Case summary: We report the case of a 60-year-old man suffering from symptomatic paroxysmal AF. The patient had a history of cold-induced urticaria without occurrence of systemic reactions to date. After successful pulmonary vein isolation (PVI) using cryoenergy, post-interventional oesophagogastroduodenoscopy and endosonography revealed newly occurred oedema in the middle oesophagus with inclusion of all oesophageal wall layers. Due to missing peri-atrial lesions, activation of cold urticaria during cryoablation rather than procedure-associated alterations was diagnosed. The patient reported no systemic or gastrointestinal symptoms after PVI. Discussion: We could demonstrate that cold urticaria can manifest as oesophageal angio-oedema in AF patients undergoing cryoablation. Therefore, these patients should be carefully considered for an alternative energy source for PVI or premedication with antihistamines when using cryoenergy.